2015
DOI: 10.1159/000375439
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Imaging Findings in Infants with Congenital Cytomegalovirus Infection: Relation to Trimester of Infection

Abstract: Background: Congenital cytomegalovirus (cCMV) infection early in pregnancy may result in major disabilities. Cerebral abnormalities detected using cranial ultrasound (cUS) and magnetic resonance imaging (MRI) have been related to neurological sequelae. Objective: To evaluate the additional value of MRI and assess the relationship between time of infection during pregnancy and outcome in infants with cCMV infection. Methods and Study Design: Demographic and clinical data were collected in infants with cCMV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
(35 reference statements)
4
29
1
1
Order By: Relevance
“…We believe that a rating scale is more helpful in categorizing the neurological risk. A recent retrospective study showed a relationship between the severity of neonatal neuroimaging and neurodevelopment in 36 infants with cCMV (26 symptomatic) [8]. All 5 patients with a normal US had a normal outcome, which is consistent with our and other studies [24], and 1 of 16 infants with mild US abnormalities (germinolysis and LSV) had polimicrogyria on MRI and a poor outcome.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We believe that a rating scale is more helpful in categorizing the neurological risk. A recent retrospective study showed a relationship between the severity of neonatal neuroimaging and neurodevelopment in 36 infants with cCMV (26 symptomatic) [8]. All 5 patients with a normal US had a normal outcome, which is consistent with our and other studies [24], and 1 of 16 infants with mild US abnormalities (germinolysis and LSV) had polimicrogyria on MRI and a poor outcome.…”
Section: Discussionsupporting
confidence: 88%
“…Our data confirm that findings traditionally deemed as nonpathological [6], such as mild ventriculomegaly, LSV or caudothalamic germinolysis, do not rule out brain involvement and a risk of SNHL or other sequelae [6,8,22,23]. While a completely normal US (as performed and interpreted by a clinician with adequate expertise) is able to predict a good outcome, in cases with the abovementioned subtle changes, investigation of CNS involvement should be completed by MRI.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…(10) kranyal ultrasonografinin nöronal migrasyon anomalilerini tespit etme oranının düşük olduğunu belirtmiştir. Ayrıca, yazarlar migrasyon anomalisi, periventrikü-ler kalsifikasyon, beyaz cevher kistleri, serebellar hipoplazi ve ventrikulomegali varlığını "ağır nöroradyolojik bulgular" olarak tanımlamışlar ve bu bulguların varlığının birinci trimester enfeksiyonuna ve yüksek mortaliteye işaret ettiğini belirtmişlerdir (10). Sunduğumuz olguda migrasyon anomalisinin kranyal ultrasonografi ile görüntülenebilmiş olması nörolojik hasarın ciddiyeti açısından anlamlıdır.…”
Section: Discussionunclassified